Chronological and geomorphological investigation of fossil debris-covered glaciers in relation to deglaciation processes: A case study in the Sierra de La Demanda, northern Spain. (15th August 2017) - ,; Aumaître, Georges; Bourlès, Didier; Keddadouche, Karim; Fernández-Fernández, José M.; Palacios, David; García-Ruiz, José M.; Andrés, Nuria; Schimmelpfennig, Irene; Gómez-Villar, Amelia; Santos-González, Javier; Álvarez-Martínez, Javier; et al.
Abstract: In this study, fossil debris-covered glaciers are investigated and dated in the Sierra de la Demanda, northern Spain. They are located in glacial valleys of approximately 1 km in length, where several moraines represent distinct phases of the deglaciation period. Several boulders in the moraines and fossil debris-covered glaciers were selected for analysis of 10 Be surface exposure dating. A minimum age of 17.8 ± 2.2 ka was obtained for the outermost moraine in the San Lorenzo cirque, and was attributed to the global Last Glacial Maximum (LGM) or earlier glacial stages, based on deglaciation dates determined in other mountain areas of northern Spain. The youngest moraines were dated to approximately 16.7 ± 1.4 ka, and hence correspond to the GS-2a stadial (Oldest Dryas). Given that the debris-covered glaciers fossilize intermediate moraines, it was deduced that they developed between the LGM and the Oldest Dryas, coinciding with a period of extensive deglaciation. During this deglaciation phase, the cirque headwalls likely discharged large quantities of boulders and blocks that covered the residual ice masses. The resulting debris-covered glaciers evolved slowly because the debris mantle preserved the ice core from rapid ablation, and consequently they remained active until the end of the Late Glacial or the beginning of the Holocene (for the San Lorenzo cirque) and the Holocene Thermal Maximum (for the Mencilla cirque). The north-facing part of the Mencilla cirque ensured longer preservation of the ice core. Highlights: Geomorphological survey allowed identifying fossil debris-covered glaciers and differentiating them from rock glaciers. First chronology of debris-covered glaciers and deglaciation in the Sierra de la Demanda based on 10 Be dating. 10 Be ages reveal an Oldest Dryas advance in the San Lorenzo cirque. Debris-covered glaciers developed during the deglaciation after the LGM, but prior to the Oldest Dryas. The debris mantle allowed the residual ice masses to endure until the early Holocene and even the Holocene Thermal Maximum.